The Impact of the Makassar Recover Program on COVID-19 Response - Humaidid Muhajir; Aswar Annas (Magister Administrasi Publik, 2023)
The spread of COVID-19 in Makassar City has increased the death rate, affected people's behavior, and crippled the economy. Various efforts have been made to mitigate it, including by implementing the Makassar Recover policy. Using a qualitative descriptive approach, this research will provide an overview of the impact of the Makassar Recover program on handling COVID-19. Primary data sources are collected through interviews with informants while secondary data sources are collected through document review of Recover Ecosystem documents. The results showed that the Makassar Recover program from the Health Immunity dimension impacted increasing community immunity through vaccination and the presence of a COVID hunter task force involved in providing social assistance and establishing treatment posts. The government also handles triage, testing, tracing, and treatment through the Recovery Task Force. The Social Adaptation Dimension impacts changing people's lifestyles to be healthier. Activities are carried out, namely sterilizing 509 social facilities and public facilities by spraying disinfectants, preparing 1,500 free handwashing stations and body temperature measuring devices, and providing educational media and a COVID-19 call center for citizens. The Economic Recovery Dimension impacts the formation of new business actors. Activities are carried out to form 5,000 start-up halls as new business actors, as many as 13,277 MSME players, and 1,604 cooperative units are activated and given capital.